Evaluation of complete security systems, aviation - Авдєєв, О.М. (Proceedings of National Aviation University (archive), 2009)
Considered to the questions of a level detection of completeness of safety of an engineering system which are used at formation and control of technical maintenance processes of a modern aircraft.